Individual, Social and Cultural Factors Among Religion Conversion Process: Live Experience of Converts in Indonesia - Mukaromah, Siti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The decision to convert is a personal choice for every non-Muslim individual, where this process often involves various stages that are often full of challenges. Someone who decides to convert means that they are ready to let go of their identity as a follower of their previous religion, and accept and adapt to the identity and teachings of the new religion. This article examines the life experiences of converts regarding the process of religious learning that they receive after marriage, reviewed from individual, social and cultural factors. The purpose of this study is that researchers are interested in highlighting the life of someone who has converted to a religious belief because of a marriage. This study uses qualitative research with the narrative inquiry method. Participants in this study were Mr. DRB and Mrs. IR. The results of the study found that participants who underwent the process of converting to a religious belief were influenced by several factors, namely 1) individual factors, due to the background of the participant's family who was not very religious, since birth the participant had never been directed or taught about a religion by his parents. 2) social factors, both participants converted because they met someone who was Muslim in an organization and in a field of work. 3) Cultural factors, that initially participants found it very difficult to adapt to the culture in their environment, because previously participants had never followed Islamic teachings and had only learned from books and other people's stories.